The Effects of Servant’s Leadership and Work Loyalty on Teacher’s Performance - Atun, Waldatun Thai; Hanafi, M Syadeli; Faturohman, Nandang (PPSDP International Journal of Education, 2023)
This study’s objective is to investigate the impact of servant leadership and work loyalty on teacher’s performance. This research employs a quantitative method of verification. Instrument in this investigation, a Likert scale-based questionnaire was used. The questionnaire, which contained 14 affirmative and negative statements for each variable, was distributed to 100 elementary school teachers in the Ciwandan subdistrict who were chosen using accidental sampling techniques (convenient sampling). The data collection procedure was conducted over the course of two months, beginning with the distribution of a questionnaire. Using version 3.0 of the Smart PLS software, each variable’s data was analysed. The results of the study show that servant leadership has a significant effect on teacher’s performance (p<0.05), work loyalty has a significant effect on teacher’s performance (p<0.05), and servant leadership mediated by work loyalty has a significant effect on teacher’s performance (p<0.05). further study will yield a blueprint for expanding school-based leadership development programs.